1999
DOI: 10.1159/000023344
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coeliac Disease in Patients with Thyroid Autoimmunity

Abstract: The occurrence of autoimmune thyroid disorders among patients with coeliac disease (CD) is well documented, but the exact prevalence of CD among patients with autoimmune thyroid diseases (ATD) is as yet unclear. We screened 150 newly diagnosed patients with ATD by serum endomysial antibody detection (EmA). In 5 subjects (3.3%) EmA positivity was found; all underwent jejunal biopsy. On gluten-free diet an excellent clinical and histological response was recorded with an improvement of hypothyroidism and reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 15 publications
2
61
1
5
Order By: Relevance
“…Additionally, in our study, the prevalence rate of CD in patients with AT was higher than in the previous studies (mean value 3.7%) [11][12][13][14] . This might be associated with the higher prevalence rate of CD in Turkish population.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Additionally, in our study, the prevalence rate of CD in patients with AT was higher than in the previous studies (mean value 3.7%) [11][12][13][14] . This might be associated with the higher prevalence rate of CD in Turkish population.…”
Section: Discussioncontrasting
confidence: 80%
“…An increased prevalence of coeliac disease has been found in patients with AT and Graves' disease [11][12][13][14] . Moreover, it has been demonstrated that many coeliacs are prone to autoimmune thyroid dysfunction [18,19] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study (10) we used an endomysial antibody to screen 150 patients with autoimmune thyroid disease; five showed a positive serology and were diagnosed as coeliacs on the basis of the jejunal biopsy. The aim of this paper was to look for signs of minor small bowel injury and immunohistochemical markers of gluten sensitivity in a group of ATD patients, in particular patients with Hashimoto's thyroiditis, without serological markers of CD.…”
Section: Introductionmentioning
confidence: 99%